Physical Activity Patterns of Students Before and After the Covid 19 Pandemic in Susukan High School - Hidayat, Dede; Rustandi, Endi; Yudha, Brio Alfatihah Rama (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The aim of the study was to find out the pattern of physical activity of students before, during and after the Covid 19 pandemic at SMAN 1 Susukan, Cirebon Regency. This type of descriptive research. The population is 816 students. The sampling technique uses simple random sampling. Sample 100 students. The test uses the PAQ-A test. The data analysis technique uses descriptive statistics. The results of the study are the Physical Activity Patterns of Students at SMAN 1 Susukan After the Covid 19 Pandemic are as follows: Physical activity during free time is 57.62%, physical activity after school once a week is 41%, in 7 days finally, after the covid 19 pandemic, in the afternoon you exercise, do physical activity 1 time a week as much as 48%, often do physical activity 2-3 times a week as much as 48%, sometimes do physical activity as much as 49% a week, and never doing physical activity as much as 32.34%. Thus it can be concluded that the physical activity pattern of SMA 1 Susukan students before the covid 19 pandemic was never doing physical activity, during the pandemic once a week, and after the covid 19 pandemic was never doing physical activity.